BACTERIAL CULTURE PROFILE ON THROAT SWAP OF PATIENTS WITH ACUTE RESPIRATORY TRACT INFECTION AT KALUMPANG HEALTH CENTER TERNATE CITY - Erpi Nurdin; Mukhtasyam Zuchrullah; Fifi B Umagapi (Jurnal Inovasi Pendidikan dan Sains, 2023)
Abstract: Respiratory tract infection is a common disease in society, and is one of the highest causes of death in children under 5 years of age (22.30%). Acute respiratory tract infections are divided into lower respiratory tract infections and upper respiratory tract infections. This infectious disease can be carried out by bacteriological examination using selective media to see the bacterial species. The aim of the research was to determine the bacterial culture profile in throat swabs of patients with acute respiratory infections at the Kalumpang Community Health Center, Ternate City using selective media, biochemical tests and gram staining. Research conducted using descriptive methods. Based on data on the characteristics of the Acute Respiratory Infection (ARI) patients studied, there were 17 men (57%) and 13 women (43%), while the age group with the most sufferers was in the 1-10 year age range, namely 9 people (30%) and then in the age range >50 years, namely 8 people (27%). Meanwhile, the percentage of culture profile findings from the bacterial species Stapylococcus aureus was 50%, Streptococcus pygones 33%, Pseudomonas aeruginosa 7%, Corynebacterium diphtheriae 10%. Found 98% gram positive bacteria and 2% gram negative bacteria. From the research results, it can be concluded that the most common bacterial culture profile in the throat swabs of upper respiratory tract infection patients is gram-positive bacteria consisting of the species Stapylococcus aureus, Streptococcus pygones, and Corynebacterium diphtheriae. The gram negative bacterial profile obtained was Pseudomonas aeruginosa. Keywords : Acute Respiratory Infections, throat swab, culture, bacteria